FEASIBILITY OF USING A GEOINFORMATION TABLET TO PROVIDE GEOSPATIAL SUPPORT FOR TROOPS (FORCES) - Lytvynenko, N.; Korenets, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The armed aggression of the russian federation against Ukraine, as well as the need to reform the state's defense sector, should become the main factors in creating a modern system of geospatial support for the Armed Forces of Ukraine. An important component of high-quality and timely geospatial support of the Armed Forces is the clear organization of the entire complex of topographic-geodetic and navigation works in the field using modern devices for collecting, processing and storing geospatial data, one of that is a geoinformation tablet, the using of it can significantly increase the efficiency and quality of performance of tasks as assigned. Currently, mobile geoinformation systems designed for creating, editing and updating electronic maps and databases in the field in real time have become widespread in various branches of state administration, production and services; inventory, maintenance of material assets; documentation of the circumstances of events by emergency services; spatial analysis and decisionmaking, etc. The paper proposes the main functional capabilities of geoinformational tablet in accordance with the main tasks of topographical and navigational support of troops (forces): determination of exact geoposition; creation, editing and updating of digital maps and databases in the field in real time; performance of basic cartometric and geodetic tasks; plotting the combat situation and the enemy's intelligence targets (objects) on a digital map of the area; visualization of digital terrain models in three-dimensional space together with objects of the operational situation; providing access to the geoinformation portal, etc. The geoinformation tablet must be compatible with existing and prospective management systems (tools) and use specialized software to perform tasks as intended.
Keywords: geoinformation tablet, geospatial support of troops (forces), digital map, electronic map, geoportal